Formation of Citrus Canker Lesions - Jamie D. Burrow; Megan M. Dewdney; Ajia M. Paolillio; Tim D. Riley (EDIS, 2019)
Citrus canker is a non-systemic bacterial disease that affects citrus trees in both the citrus nursery and in commercial plantings. This poster is designed to assist citrus nursery workers in the identification of citrus canker. This one-page document was written by Jamie Burrow, Megan Dewdney, Ajia Paolillo, and Tim Riley and published by the UF/IFAS Plant Pathology Department. http://edis.ifas.ufl.edu/pp346